Chimeric and Pseudotyped Parvoviruses Minimize the Contamination of Recombinant Stocks with Replication-Competent Viruses and Identify a DNA Sequence That Restricts Parvovirus H-1 in Mouse Cells - Wrzesinski, Claudia (American Society for Microbiology, 2003)
Recent studies demonstrated the ability of the recombinant autonomous parvoviruses MVMp (fibrotropic variant of the minute virus of mice) and H-1 to transduce therapeutic genes in tumor cells. However, recombinant vector stocks are contaminated by replication-competent viruses (RCVs) generated during the production procedure. To reduce the levels of RCVs, chimeric recombinant vector genomes were designed by replacing the right-hand region of H-1 virus DNA with that of the closely related MVMp virus DNA and conversely. Recombinant H-1 and MVMp virus pseudotypes were also produced with this aim. In both cases, the levels of RCVs contaminating the virus stocks were considerably reduced (virus was not detected in pseudotyped virus stocks, even after two amplification steps), while the yields of vector viruses produced were not affected. H-1 virus could be distinguished from MVMp virus by its restriction in mouse cells at an early stage of infection prior to detectable viral DNA replication and gene expression. The analysis of the composite viruses showed that this restriction could be assigned to a specific genomic determinant(s). Unlike MVMp virus, H-1 virus capsids were found to be a major determinant of the greater permissiveness of various human cell lines for this virus.